2021
DOI: 10.1051/0004-6361/202142638
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the non-thermal pressure and hydrostatic bias in galaxy clusters

Abstract: We present a modelization of the non-thermal pressure, PNT, and we apply it to the X-ray (and Sunayev-Zel’dovich) derived radial profiles of the X-COP galaxy clusters. We relate the amount of non-thermal pressure support to the hydrostatic bias, b, and speculate on how we can interpret this PNT in terms of the expected levels of turbulent velocity and magnetic fields. Current upper limits on the turbulent velocity in the intracluster plasma are used to build a distribution 𝒩(< b)−b, from which we infer tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Overall, we can see that the hydrostatic mass bias does not significantly affect the estimated sparsity, with a bias of the order of few per cent and in most cases compatible with a vanishing bias with only a few exceptions. This is consistent with the results of the recent analysis based on observed X-ray clusters presented in Ettori & Eckert ( 2022 ), which yield sparsity biasses at the per cent level and consistent with having no bias at all. Ho we v er, we hav e seen in the case of the WL mass bias that even though the effect on the measured sparsity remains small, the scatter around the true sparsity can severely affect the efficiency of the detector at identifying recent mergers.…”
Section: Hydrostatic Mass Biassupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, we can see that the hydrostatic mass bias does not significantly affect the estimated sparsity, with a bias of the order of few per cent and in most cases compatible with a vanishing bias with only a few exceptions. This is consistent with the results of the recent analysis based on observed X-ray clusters presented in Ettori & Eckert ( 2022 ), which yield sparsity biasses at the per cent level and consistent with having no bias at all. Ho we v er, we hav e seen in the case of the WL mass bias that even though the effect on the measured sparsity remains small, the scatter around the true sparsity can severely affect the efficiency of the detector at identifying recent mergers.…”
Section: Hydrostatic Mass Biassupporting
confidence: 92%
“…Deviations from this condition can induce a radially dependent bias on the cluster masses (see e.g. Biffi et al 2016 ;Eckert et al 2019 ;Ettori & Eckert 2022 ), thus affecting the estimation of the cluster's sparsity. The hydrostatic mass bias has been studied in Biffi et al ( 2016 ), who have realized cosmological zoom N -body/hydro simulations of 29 clusters to e v aluate the bias of masses at o v erdensities = 200, 500, and 2500 (in units of the critical density) for Cool Core (CC) and No Cool Core (NCC) clusters, as defined with respect to the entropy in the core of their sample, as well as for regular and disturbed clusters defined by the offset of the centre of mass and the fraction of substructures.…”
Section: Hydrostatic Mass Biasmentioning
confidence: 99%
“…[41] classify this cluster as dynamically active based on the central entropy estimates. However, the X-COP clusters are on average relaxed systems due to the selection applied [41], and this has been confirmed from the observed hydrostatic bias and the negligible amount of non-thermal pressure support [44] (see also [46], which reaffirmed the earlier conclusions using a new method to estimate the hydrostatic bias and non-thermal pressure).…”
Section: Recap Of Resultssupporting
confidence: 71%
“…Therefore, several studies investigated the impact of modifications to the way the mass observable relations are determined on the cluster abundance observable with relative success when trying to account for it as solution to the σ 8 discrepancy. One line targeted the cooling and heating processes closely related to cluster mass determination, such as the work by McDonald et al (2017), Henson et al (2017), and Mummery et al (2017), who showed, using hydrodynamic simulations, that using a different mass weighted cooling scheme or taking into account non-thermal pressure coming from bulk and turbulent motions of gas in the intracluster medium (Shi et al 2016;Ettori & Eckert 2022) could reduce the hydrostatic bias, although still below the amount needed to reconcile the observed cluster number count with CMB. Another study was performed by the second release of the Planck collaboration (Planck Collaboration et al 2016a) on the impact of the signal-to-noise ratio (S/N) on the number of detections, but found that it would be necessary for Planck to have missed nearly 40% of the clusters with predicted SZ S/N > 7 in order for the SZ and CMB cluster number count to match with a level of scatter with cluster structure inconsistent with the predictions of current hydrodynamical simulations.…”
Section: Introductionmentioning
confidence: 99%